Intrathecal bupivacaine versus chloroprocaine for transvaginal cervical cerclage placement: a retrospective cohort study. (May 2022) - Mims, S.C.; Zanolli, N.C.; Fuller, M.; Habib, A.S.
Highlights: Cervical cerclage placement is commonly performed under spinal anesthesia. Retrospective analysis comparing spinal bupivacaine vs. chloroprocaine. Chloroprocaine was associated with shorter time to hospital discharge. Inadequate anesthesia was not significantly different between the groups. Abstract: Background: Bupivacaine is commonly used in spinal anesthesia for cervical cerclage placement, but its long duration of action can delay hospital discharge. Chloroprocaine has a short duration of action and has re-emerged as an agent for ambulatory neuraxial anesthesia. There are limited data comparing intrathecal bupivacaine and chloroprocaine when used for cerclage placement. This retrospective study compares the time to hospital discharge between these drugs when used in spinal anesthesia for cervical cerclage placement. Methods: A retrospective analysis of patients who underwent transvaginal cerclage placement under neuraxial anesthesia with intrathecal hyperbaric bupivacaine or plain chloroprocaine between January 1, 2015 and October 31, 2020. The primary outcome was the time to hospital discharge. Secondary outcomes included the incidence of inadequate anesthesia, postoperative pain scores and postoperative neurologic symptoms. Results: Three hundred and sixty patients were included in the final analysis (bupivacaine n=236, chloroprocaine n=124). The median (IQR) intrathecal dose was 7.5 (7.5, 9) mg and 45 (45, 50) mg in the bupivacaine and chloroprocaine groups respectively. The time (median [IQR]) from spinal anesthesia to hospital discharge was significantly shorter in the chloroprocaine group compared with the bupivacaine group (218 [180, 253] vs. 370 [309, 424] min, P <0.001). There were no significant differences between the groups for secondary outcomes and neither group had a patient report neurologic symptoms. Conclusion: When utilized in spinal anesthesia for transvaginal cervical cerclage placement, chloroprocaine may reduce the time to discharge while providing comparable anesthesia to that provided by bupivacaine.